KEABSAHAN PERJANJIAN JUAL BELI TANAH DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA (STUDI PUTUSAN NOMOR: 15/PDT.G/2020/PN KFM) - Intan Thesalin Konay; Darius Mauritsius; Husni Kusuma Dinata (Petitum Law Journal, 2026)
This study examines the validity of an oral land sale and purchase agreement in the Kefamenanu District Court Decision Number 15/Pdt. G/2020/PN Kfm. Normatively, the relationship between the Plaintiff and the late Yacob Maniagala has met the requirements for a valid agreement in accordance with Article 1320 of the Civil Code, which includes the consent of all parties, legal capacity, clear objects, and legitimate purposes. However, the panel of judges rejected the application on the grounds that: the purchase receipt was considered unilateral because it was only signed by the seller without involving authorized officials such as PPAT or Lurah; the transaction violated the provisions of Article 37 of Government Regulation Number 24 of 1997 which requires a Land Deed Official, deed for the transfer of land rights; and factual ownership for nine years is not considered valid evidence without a land title certificate. This decision shows a striking difference between civil law recognition of oral agreements and agrarian lawsuits related to administrative formalities. Even though the procedures have been met, there is still substantive injustice to buyers in good faith. Thus, this study encourages the need for reform in the land registration system to accommodate informal sales practices that often occur in society.